Pertahankan Tradisi Masyarakat Patang Balimau di Tengah Perkembangan Zaman - Sindi Septia Hasnida; Solfema Solfema; Lili Dasa Putri (Journal Innovation In Education, 2025)
The Patang Balimau tradition is one of the cultural heritages of the Minangkabau people, West Sumatra, which has symbolic value as a form of self-purification before entering the holy month of Ramadan. Patang Balimau is a communal bathing ritual using water mixed with lime, accompanied by prayers that have philosophical value. This tradition symbolizes the intention to purify oneself, both physically and spiritually, before fasting. In the midst of rapid technological developments and foreign cultural influences, Patang Balimau faces big challenges in maintaining its existence. This article focuses on the meaning, practice, as well as various challenges and efforts in preserving the Patang Balimau tradition.